THE URGENCY OF COMPULSORY MILITARY SERVICE IN THE FRAMEWORK OF MAINTAINING INDONESIA'S NATIONAL SECURITY - Gio Zaky Asadul Haq; Bambang Widarto; Diding Rahmat (JILPR Journal Indonesia Law and Policy Review, 2026)
National security is a fundamental prerequisite for upholding sovereignty, territorial integrity, and the safety of all Indonesians. In an increasingly complex global context, Indonesia faces various potential threats, both traditional threats such as military aggression and non-traditional threats such as terrorism, separatism, cyber threats, and natural disasters. Indonesia's strategic geographic location, as the world's largest archipelagic nation, demands a comprehensive, adaptive, and people-driven defense system. This study examines the urgency or necessity of implementing mandatory military service to safeguard Indonesia's national security and compares the implementation of mandatory military service in Thailand and South Korea as a policy reference for Indonesia. The results indicate that mandatory military service in Indonesia is highly urgent in increasing public preparedness, building strategic defense reserves, and fostering a spirit of national defense. However, its implementation requires a clear legal basis, thorough planning, and readiness of infrastructure and human resources. Thus, compulsory military service can be a strategic instrument to strengthen the overall defense system in accordance with Indonesia's geostrategic characteristics.